Spontaneous Rupture of Splenic Varices: A Rare but Lethal Complication of Portal Hypertension from Cirrhosis. Issue 2 (March 2014) - Yang, CH; Huang, YC; Kuo, WT
Intra-abdominal varices rupture is a rare but catastrophic complication in cirrhosis. We report our near-miss experience in a woman presenting with acute abdominal pain and shock. This 55-year-old cirrhotic woman presented with sudden onset of epigastric pain. On arrival, her blood pressure was 57/49 mmHg and physical examination revealed epigastric tenderness without rebounding tenderness. Emergency ultrasonography (EUS) showed intra-abdominal haemorrhage. Computed tomography revealed haemoperitoneum but no extravasation of contrast medium. She received conservative treatment first but laparotomy later for ongoing bleeding. Surgeon identified and ligated a ruptured splenic varix and she was discharged home after nine days of hospitalisation. This case report illustrates the use of bedside EUS in cirrhotic patients presenting with acute abdominal pain. (Hong Kong j.emerg.med. 2014;21:120-123)